2010
DOI: 10.1183/09031936.00015710
|View full text |Cite
|
Sign up to set email alerts
|

Malignant pleural effusion cells show aberrant glucose metabolism gene expression

Abstract: Malignant pleural effusion (MPE) accompanying lung adenocarcinoma indicates poor prognosis and early metastasis. This study aimed to identify genes related to MPE formation.Three tissue sample cohorts, seven from healthy lungs, 18 from stage I-III lung adenocarcinoma with adjacent healthy lung tissue and 13 from lung adenocarcinomas with MPE, were analysed by oligonucleotide microarray. The identified genes were verified by quantitative realtime PCR (qRT-PCR), immunohistochemical staining, and immunofluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 37 publications
6
14
0
Order By: Relevance
“…However, integrins connect cells to components of the extracellular matrix or to counter receptors on other cells mediating cell adhesion, migration, and other cell–cell contact. It is very likely the overexpression of ITGA9 in SCLCs is also linked to the high metastatic nature of lung cancer cells, and ITGA9 has recently been reported to promote tumor cell adhesion and migration [48]. Thus, CD24 and ITGA9 are very likely among the factors that make the SCLC cells highly prone to metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…However, integrins connect cells to components of the extracellular matrix or to counter receptors on other cells mediating cell adhesion, migration, and other cell–cell contact. It is very likely the overexpression of ITGA9 in SCLCs is also linked to the high metastatic nature of lung cancer cells, and ITGA9 has recently been reported to promote tumor cell adhesion and migration [48]. Thus, CD24 and ITGA9 are very likely among the factors that make the SCLC cells highly prone to metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Oh et al [30] demonstrated the presence of T k in BM-derived IPCs under high-glucose conditions. Aberrant T k has been reported to participate in glucose metabolism in malignant pleural effusion cells [31]. T k variants and reduced activities of T k enzyme were found in diabetic patients [32-33].…”
Section: Relationship Between Thiamine and Diabetes Mellitusmentioning
confidence: 99%
“…As PET-CT is becoming more widely used, the research on its use in the diagnosis of pulmonary GGN is increasing (1). In vitro and in vivo experiments have demonstrated that lung cancer cells have higher levels of glucose metabolism as compared with normal tissue cells (19). Furthermore, as an effective means of identification and diagnosis, 18 F-FDG PET-CT is important in the diagnosis of primary lung cancer (20).…”
Section: Discussionmentioning
confidence: 99%